Quantitative Super-Resolution Microscopy of the Mammalian Glycocalyx - Möckl, Leonhard; Pedram, Kayvon; Roy, Anish R.; Krishnan, Venkatesh; Gustavsson, Anna Karin; Dorigo, Oliver; Bertozzi, Carolyn R.; Moerner, W. E. (Developmental Cell, 2019)
The mammalian glycocalyx is a heavily glycosylated extramembrane compartment found on nearly every cell. Despite its relevance in both health and disease, studies of the glycocalyx remain hampered by a paucity of methods to spatially classify its components. We combine metabolic labeling, bioorthogonal chemistry, and super-resolution localization microscopy to image two constituents of cell-surface glycans, N-acetylgalactosamine (GalNAc) and sialic acid, with 10–20 nm precision in 2D and 3D. This approach enables two measurements: glycocalyx height and the distribution of individual sugars distal from the membrane. These measurements show that the glycocalyx exhibits nanoscale organization on both cell lines and primary human tumor cells. Additionally, we observe enhanced glycocalyx height in response to epithelial-to-mesenchymal transition and to oncogenic KRAS activation. In the latter case, we trace increased height to an effector gene, GALNT7. These data highlight the power of advanced imaging methods to provide molecular and functional insights into glycocalyx biology. Nearly every cell in the human body is encapsulated by an extramembrane glycosylated compartment—the glycocalyx—that is the cell's first point of contact with the extracellular environment. Möckl et al. combine bioorthogonal chemistry with quantitative super-resolution imaging to investigate glycocalyx nanoscale organization and its relationship to oncogenic cellular transformation.
CRIS-Team Scopus Importer:2024-09-09
Keywords: bioorthogonal chemistry; GALNT7; glycobiology; glycocalyx; KRAS; membrane biophysics; metabolic labeling; ovarian cancer; pancreatic adenocarcinoma; super-resolution microscopy